Efficient construction of pyrrolo[1′, 2′:1, 2]azocino[4, 5-c]quinolines via cascade cycloaddition and annulation reaction. Issue 20 (9th September 2019) - Wu, Wen-Tao; Han, Ying; Sun, Jing; Yan, Chao-Guo
Abstract : Novel polysubstituted pyrrolo[1′, 2′:1, 2]azocino[4, 5- c ]quinolines were efficiently synthesized by a three-component reaction in refluxing methanol and a sequential domino annulation in refluxing acetonitrile. Abstract : Novel polysubstituted pyrrolo[1′, 2′:1, 2]azocino[4, 5- c ]quinolines were efficiently synthesized by a one-pot three-component reaction of proline, isatins and chalcones in refluxing methanol and by a sequential domino annulation reaction with methyl propiolate in refluxing acetonitrile. The reaction with isatins without an N -protecting group afforded hexahydropyrrolo[1′, 2′:1, 2]azocino[4, 5- c ]quinolines, while the reaction with N -benzylisatins gave octahydropyrrolo[1′, 2′:1, 2]azocino[4, 5- c ]quinolones with an additional propiolate unit connecting to a dihydropyridyl ring. The reaction mechanism with domino [3 + 2]cycloaddition, ring-expansion and annulation processes was rationally proposed for the formation of polycyclic products.